Elections as popular culture in Asia - Chua, Beng Huat (Politics in Asia series, 2007)
"The chapters in this book analyse electioneering activities in nine Asian countries in terms of popular cultural practices in each location, ranging from updated traditional cultures to mimicry and caricatures of present day television dramas. In presenting political election as an expression of popular culture, Elections as Popular Culture in Asia portrays electoral behaviour as a meaningful cultural practice. As such, this book will appeal to students and scholars of political science and cultural studies alike, as well as those with a more general interest in Asian studies.